Implementation of Game Methods to Increase Students' Interest and Understanding in Learning Aqidah Akhlak at MIS Mathla'ul Anwar Muruy - Nurajizah, Yayu; Hidayati, Yani (DEEP LEARNING: Journal of Educational Research, 2025)
This study aims to analyze the effectiveness of game-based methods in enhancing students' interest and understanding of Aqidah Akhlak learning, particularly in the Asmaul Husna material, in the 3rd grade of MIS Mathla'ul Anwar Muruy.The study of Aqidah Akhlak is often considered less interesting by students, so innovative strategies are needed to enhance their learning motivation.The game method is applied as a solution to create a more interactive and enjoyable learning atmosphere. This study used a quantitative approach with data collection techniques through pre-test, post-test, observation, and questionnaire. Data analysis was conducted using the paired sample t-test statistical test to measure the significance of the increase in student understanding before and after the application of the game method. The results showed a significant increase in students' understanding after the method was applied, with the average post-test score increasing compared to the pre-test. Observation during the learning process also showed that students were more active, enthusiastic, and easier to remember and understand the meaning of Asmaul Husna. In addition, the questionnaire results revealed that 90% of students felt more interested in learning with the game method than the conventional method. In addition to the impact on academic understanding, the game method also has a positive social contribution. Students are more actively interacting, cooperating, and communicating with friends and teachers during the learning process. Thus, this method not only improves cognitive aspects but also affective aspects in Aqidah Akhlak learning. This study recommends the wider use of game methods in Islamic learning and the development of more innovative game variations so that they can be applied at various levels of education.